Reduced mRNA and Protein Expression Levels of Tet Methylcytosine Dioxygenase 3 in Endothelial Progenitor Cells of Patients of Type 2 Diabetes With Peripheral Artery Disease - Zhao, Shi; Jia, Ting; Tang, Yang; Zhang, Xiaotong; Mao, Hong; Tian, Xiaojia; Li, Rui; Ma, Lu; Chen, Guoxun (Frontiers in Immunology, 2018)
Endothelial progenitor cells (EPCs) with immunological properties repair microvasculature to prevent the complications in patients with diabetes. Epigenetic changes such as DNA methylation alter the functions of cells. Tet methylcytosine dioxygenases (TETs) are enzymes responsible for the demethylation of cytosine on genomic DNA in cells. We hypothesized that EPCs of diabetic patients with peripheral artery disease (D-PAD) might have altered expression levels of TETs. Subjects who were non-diabetic (ND, n=22), with diabetes only (D, n=29) and with D-PAD (n=22) were recruited for the collection of EPCs, which were isolated and subjected to analysis. The mRNA and protein expression levels of TET1, TET2, and TET3 were determined using real-time PCR and immunoblot, respectively. The TET1 mRNA expression level in ND group was lower than that in the D and D-PAD groups. The TET3 mRNA level in the ND group was higher than that in the D group, which was higher than that in the D-PAD group. The TET1 protein level in the D-PAD group, but not the D group, was higher than that in the ND group. The TET2 protein level in the D-PAD group, but not the D group, was lower than that in the ND group. The TET3 protein level in the ND group was higher than that in the D group, which was higher than that in the D-PAD group, which is the lowest among the three groups. The changes of TETs protein levels were due to the alterations of their transcripts. These probably lead to epigenetic changes, which may be responsible for the reductions of EPCs numbers and functions in patients with the D-PAD. The expression pattern of TET3 mRNA and TET3 protein in EPCs may be a biomarker of angiopathy in diabetic patients.